Addressing Challenges in Converting Grant-Funded Infrastructures to Broadly Used Research Resources - Rolland, Betsy; Geiger, Ann M (Cancer epidemiology, biomarkers & prevention, 2019)
The NCI invests heavily in research resources to serve the research community, including datasets, biospecimen banks, and networks of institutions in which clinical trials and other human subjects research are conducted. These resources often begin as grant-funded infrastructure initiated by scientists based on their own scientific interests, with a subsequent recognition of additional scientific uses. Although converting existing project-specific research activities into research resources may appear efficient in terms of time and financial investment, challenges can arise that undermine this efficiency and jeopardize future use. Here, we describe three challenges in the conversion process: (i) project-based infrastructure versus a research resource for a broader research community; (ii) complexity versus ease of use; and (iii) individual professional goals versus research resource priorities. We use our experience with the NCI-funded Cancer Research Network, particularly the Virtual Data Warehouse, to illustrate each challenge, concluding with strategies to mitigate each one. As studies grow in size and complexity, an ever-increasing volume of data, biospecimens, and human subjects research networks will be available for conversion to resources for scientific questions beyond those originally proposed. Addressing likely challenges thoughtfully can result in a more efficient conversion process and ultimately greater scientific impact.